18F-FDG PET/CT of Double Expressor High-Grade B-Cell Lymphoma in an Isolated Chest Wall Mass. (January 2021) - Sharma, Punit
Abstract : Abstract: 18 F-FDG PET/CT is now an integral part of management of high-grade B-cell lymphoma. It is used for staging, response evaluation, restaging, and surveillance. Although high-grade B-cell lymphoma most commonly presents with involvement of the lymph nodes, spleen, liver, and bone marrow, chest wall involvement is very rare. We present the staging 18 F-FDG PET/CT findings in a case of an 82-year-old woman with double expressor high-grade B-cell lymphoma of isolated presternal anterior chest wall mass.